2017
DOI: 10.1371/journal.pone.0172342
|View full text |Cite
|
Sign up to set email alerts
|

Effective cataract surgical coverage: An indicator for measuring quality-of-care in the context of Universal Health Coverage

Abstract: Objective To define and demonstrate effective cataract surgical coverage (eCSC), a candidate UHC indicator that combines a coverage measure (cataract surgical coverage, CSC) with quality (post-operative visual outcome). Methods All Rapid Assessment of Avoidable Blindness (RAAB) surveys with datasets on the online RAAB Repository on April 1 2016 were downloaded. The most recent study fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 31 publications
2
97
1
7
Order By: Relevance
“…We found that PNG is below the recommended target. However, as several countries are yet to reach the recommended cataract surgery outcome targets,20 our findings are similar to other low-income, middle-income countries, indicating the continuing need for increased surgical coverage and improved outcomes potentially through increasing resources, training and personnel. Currently there are 14 practising ophthalmologists and 5 in training, most of which are based in more urban areas.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We found that PNG is below the recommended target. However, as several countries are yet to reach the recommended cataract surgery outcome targets,20 our findings are similar to other low-income, middle-income countries, indicating the continuing need for increased surgical coverage and improved outcomes potentially through increasing resources, training and personnel. Currently there are 14 practising ophthalmologists and 5 in training, most of which are based in more urban areas.…”
Section: Discussionsupporting
confidence: 74%
“…Based on available RAAB data, the median CSC is 53.7 for operable cataracts (pinhole VA <6/60) across low-income, middle-income countries in Asia, Africa and South America 20. PNG had an estimated combined national CSC of 32.3%.…”
Section: Discussionmentioning
confidence: 99%
“…The eCSC rate is a population-based measure to understand accessibility and quality of cataract surgery within populations 21. We report a high eCSC rate among non-Indigenous Australians (88.5%) suggesting that the healthcare system within Australia is close to meeting demand for cataract surgeries and further indicating an overall good quality of cataract surgical services and postoperative care for non-Indigenous Australians.…”
Section: Discussionmentioning
confidence: 69%
“…We report a high eCSC rate among non-Indigenous Australians (88.5%) suggesting that the healthcare system within Australia is close to meeting demand for cataract surgeries and further indicating an overall good quality of cataract surgical services and postoperative care for non-Indigenous Australians. Of note, comparisons of the eCSC rates with previous studies21 should be made with extreme caution as we adopted more stringent cut-offs for operable cataract (best-corrected VA <6/12 vs best-corrected VA <6/60) and postsurgery good VA outcomes (PVA ≥6/12 vs PVA ≥6/18). This definition was adopted as 6/12 is a legal requirement for driving in Australia, and lower thresholds for cataract surgery exist 23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation